A field-test battery for elite, young soccer players - Hulse, M. A.; Morris, J. G.; Hawkins, R. D.; Hodson, A.; Nevill, A. M.; Nevill, M. E. (International Journal of Sports Medicine, 2013)
The validity and reliability of a battery of field-based performance tests was examined. The opinions of coaches, fitness professionals and players (n=170, 172 and 101 respectively) on the importance of performance testing were established using a questionnaire. On 2 occasions, separated by 7 days, 80 elite, young soccer players (mean±SD [and range]: age 13.2±2.6 [8.9-19.1] years; stature 1.59±0.18 m [1.32-1.91]; body mass 50.6±17.1 [26.5-88.7] kg) completed a battery of field-based tests comprised of heart rate response to a submaximal Multi-stage fitness test, 3 types of vertical jump, sprints over 10 and 20 m, and an agility test. Physical performance testing was considered important by coaches (97%), fitness professionals (94%) and players (83%). The systematic bias ratio and the random error components of the 95% ratio limits of agreement for the first and second tests, for the U9-U11 vs. U12-U14 vs. U15-U18 age groups, were [Systematic bias (*/÷ ratio limits)]: Heart rate (Level 5): 0.983 (*/÷ 1.044) vs. 0.969 (*/÷ 1.056) vs. 0.983 (*/÷ 1.055); Rocket jump: 0998 (*/÷ 1.112) vs. 0.999 (*/÷ 1.106) vs. 0.996 (*/÷ 1.093); 10 m sprint: 0.997 (*/÷ 1.038) vs. 0.994 (*/÷ 1.033) vs. 0.994 (*/÷ 1.038); Agility test: 1.010 (*/÷1.050) vs. 1.014 (*/÷1.050) vs. 1.002 (*/÷1.053). All tests, except heart rate recovery from the Multi-stage fitness test, were able to distinguish between different ability and age groups of players (p<0.05). Thus, the field-test battery demonstrated logical and construct validity, and was shown to be a reliable and objective tool for assessing elite, young soccer players.